How Can Poetry Support the Understanding of Psychotic Experiences? – A Conceptual Review - Pearson, Mark (J Recovery Ment Health, 2020)
OBJECTIVE: The therapeutic application of poetry for those who have experienced psychosis remains under researched and potentially undervalued. This paper presents a conceptual review exploring the relationship between poetry and psychosis, based on a synthesis of existing literature. RESEARCH DESIGN AND METHODS: The review identified papers from a range of sources and disciplines. Initial searches were undertaken using databases CINAHL, PsycINFO and ASSIA; this search was then followed up with a library search for key texts and a further search for associated grey literature involving exploring blogs and conference presentations. The data was then synthesized based on methods from both narrative review and thematic analysis to generate a conceptual framework. RESULTS: The results reveal a conceptual framework comprised of three domains: i) psychotic language as meaningful poetics, ii) poetry as an expression of psychosis and iii) poetic exchange as therapeutic practice. The conceptual framework proposes that not only can psychosis be understood as meaningful poetics, but also that poetry may offer meaningful linguistic opportunities to aid the expression and narration of self and experiences. The potential for extending our understanding of the poetry in this way is analogous to forms of talking therapy, and this may be a base for extending understanding and communicative practice for a range of mental health professions. CONCLUSION: The conceptual framework suggests a novel understanding of psychosis in relation to poetry, moving away from traditional biomedical paradigms and placing importance upon individual narratives.